MANAJEMEN PEMBELAJARAN PAUD BERBASIS KEARIFAN LOKAL DALAM PERSPEKTIF FILOSOFI MERDEKA BELAJAR - Novan Ardy Wiyani (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2022)
This study aims to describe and analyze the management of PAUD learning based on local wisdom in the perspective of the philosophy of independent learning at TK Diponegoro 187 Gerduren Purwojati Banyumas. This research is a type of phenomenological research with a qualitative approach. Data were collected by interview, observation and documentation techniques. Then analyzed through the stages of data reduction, data display and verification. The results showed that the management of PAUD learning based on local wisdom in the perspective of the philosophy of independent learning was processed through three stages, namely learning planning, implementation of learning and supervision of learning based on local wisdom. In these three stages, the philosophy and spirit of independent learning are actualized with the aim that children have the ability to think logically or think critically and become creative individuals as well as character. These characters are independent, responsible, creative, innovative, love the environment, and discipline. All of these characters make the child a civilized and independent person.